O topo da distribuição salarial no Brasil: uma análise por gênero nos anos de 2005 e 2015 - Jéssica Bento de Araújo (2019)
In recent years, the importance of understanding the evolution of income distribution has gained relevance, especially among those located among the richest. In Brazil, despite the reduction in labor income inequality as a whole and, in particular between genders, inequalities persist. In this sense, the study seeks to understand possible factors that hinder the professional rise of women located at the top of the distribution of labor income, seeking to verify the presence (or not) of the glass ceiling phenomenon in the country. For this, we use data from the National Household Sample Survey (PNAD) of the Brazilian Institute of Geography and Statistics (IBGE), from 2005 and 2015, correcting the possible selection bias of women when participating in the labor market. In general, there is the existence of glass ceiling in Brazil in the period as a whole. Although gender inequalities have narrowed, the wage gap still persists. There is a reduction in the qualification differential between genders, with women more qualified than men at the top income, although with lower salary levels. In addition, the results show that being a black worker, being the main financial person in charge of the household, and spending monthly hours on significant household chores contribute to the glass ceiling. On the other hand, higher accumulation of human capital, age, being inserted in the informal sector or public administration, and living in metropolitan areas of the Southeast, South and Federal District, contribute to the reduction of obstacles to professional growth at the top income.